Social Cartography as a path to transdisciplinarity within the socio-environmental aspects of the NEXUS+ approach: a case study in the Jacaré- Curituba Settlement, Brazil - Davalos, Nelson Bernal; Oliveira, Elton S.; Santos, Roseli; Satyr, Guadalupe; Jean, Wesly; Brown, Paula Rodrigues Alves; Dalboni, Juliana; Nogueira, Daniela (Sustainability in Debate, 2024)
This article presents the results of the implementation of a “social cartography” in the INCT-Odisseia research project, in the study area of the Jacaré-Curituba agrarian reform settlement, located in the interior of the State of Sergipe, Brazil. The incorporation of social cartography as a methodological instrument in the research allowed the identification of attributes in the study area, organised using two approaches: “Analytic Hierarchy Process" (AHP) and Nexus+ (food, water, energy and socio-ecological security). Through these, it was possible to delimit the study area into agro-villages and identify more than 720 attributes or reference points, ranging from human activities to local infrastructure. The attributes were identified through action research techniques, participatory observation and collaborative research, using geographic information applications and satellite images. It was possible to generate relevant information about the study area in terms of potential, infrastructure, crops, and production, in addition to generating maps of the vulnerability situation linked to Nexus+ security (energy and water), which should be replicated since it allows highlighting the social, economic, environmental and infrastructure characteristics of a given area.